Leveraging the "String of Pearls" for strategic gains? An assessment of the Maritime Silk Road Initiative's (MSRI) economic/security nexus in the Indian Ocean Region (IOR). Issue 2 (4th May 2021) - Barton, Benjamin
ABSTRACT: Since the launch of the Maritime Silk Road Initiative (MSRI), observers have witnessed the consolidation of a growing Chinese presence in ports around the Indian Ocean Region (IOR). This growing presence has caused alarm among skeptics who view the MSRI as a second coming of the String of Pearls (SoP). Indeed, China is seen as leveraging MSRI port investments in return for national strategic and geopolitical gain, such as ultimately gaining a military foothold in MSRI ports. Regardless of China's purported intent, this paper seeks to add nuance to this debate by examining whether Beijing can actually achieve such strategic gains in the IOR via the deployment of its economic statecraft (via MSRI investments). As the paper shows, the MSRI's current rollout – as well as the inherent resistance to the strategic dimensions of this rollout – offer little in the way of empirical support to the SoP concept.